Oxygen therapy for COPD - McDonald, Christine F. (J Thorac Dis, 2014)
Chronic obstructive pulmonary disease (COPD) is a leading cause of disability and death globally, characterised by progressive breathlessness, loss of function and, in its later stages, chronic hypoxaemia. Long-term continuous oxygen therapy increases life expectancy in patients with severe resting hypoxaemia. However, there are few data to support the use of oxygen in patients with only mild hypoxaemia and more research is required to determine any benefits of oxygen supplementation in COPD in such individuals.